Production of Goat Horn Particles Reinforced Epoxy Resin Composite for Automobile Brake Pad - Dukku, M. M.; Maidawa, H.; Dogo, I. N.; Tahir, N. M.; Zadawa, M. Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
The development and evaluation of goat horn as asbestos-free friction material for the production of automotive brake pad was carried out in this work. Asbestos friction material that been used has been found to be carcinogenic and has prompted several research efforts for its replacement in brake pads application. In this research, six samples of composites were produced using goat horn particulate size of 300 µm and 600 µm as reinforced material with epoxy resin as the matrix with the following percentage compositions for specimen A, B, C, D, E, and F (21 wt% goat horn and 60 wt% epoxy resin, 21 wt% goat horn, 60 wt% epoxy resin, 26 wt% goat horn and 55 wt% epoxy resin, 26 wt% goat horn and 55 wt% epoxy resin, 31 wt% goat horn and 50 wt% epoxy resin and 31 wt% goat horn and 50 wt% epoxy resin with 3 wt% iron chips, 7 wt% silica, 4 wt% graphite, and 4 wt% CaCO3; in each sample) respectively. These specimens were made by compression molding method and subjected to mechanical and physical tests to ascertain their performance in service using standard test procedures, materials and equipment. The result showed that specimens composite samples A and B gave optimum performance for water and oil absorption of 0.725%, and 0.494%, hardness and compressive strength of 121.21 MPa and 10.313 respectively. furthermore, samples E and F gave the optimum performance for coefficient of friction (0.47) and abrasion resistance (4.297x10-6g/m) respectively. It was observed that increase in the reinforcement content increased hardness, water and oil absorption and coefficient of friction of the composite brake pad, while wear rate and compressive strength decreased. The results showed that goat horn particles are an effective replacement for asbestos in automotive brake pad application.